2018
DOI: 10.1007/s00415-018-8903-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of tissue-type metabolic content in secondary progressive multiple sclerosis: a magnetic resonance spectroscopic imaging study

Abstract: Proton magnetic resonance spectroscopy yields metabolic information and has proved to be a useful addition to structural imaging in neurological diseases. We applied short-echo time Spectroscopic Imaging in a cohort of 42 patients with secondary progressive multiple sclerosis (SPMS). Linear modelling with respect to brain tissue type yielded metabolite levels that were significantly different in white matter lesions compared with normal-appearing white matter, suggestive of higher myelin turnover (higher choli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The 1 H-MRS and MRSI methods allow quantitative measurements of brain metabolites that provide useful markers for disease investigation and longitudinal evaluations. MRS techniques have been applied to study numerous brain conditions and disorders, including brain development, 7,115 drug discovery and evaluation, 14 and several diseases and disorders, such as human immunodeficiency virus/acquired immunodeficiency syndrome, 10,[116][117][118][119] Alzheimer's disease and mild cognitive impairment, 120 multiple sclerosis, 121,122 schizophrenia, 123 Parkinson's disease, 124,125 amyotrophic lateral sclerosis, 126 fetal alcohol spectrum disorders, 127 Tourette syndrome, 128 and autism. 129,130 As discussed earlier, MRS/MRSI acquisitions are necessarily long to attain data with sufficient SNR, rendering these acquisitions susceptible to subject and scanner instabilities.…”
Section: Clinical Investigationsmentioning
confidence: 99%
“…The 1 H-MRS and MRSI methods allow quantitative measurements of brain metabolites that provide useful markers for disease investigation and longitudinal evaluations. MRS techniques have been applied to study numerous brain conditions and disorders, including brain development, 7,115 drug discovery and evaluation, 14 and several diseases and disorders, such as human immunodeficiency virus/acquired immunodeficiency syndrome, 10,[116][117][118][119] Alzheimer's disease and mild cognitive impairment, 120 multiple sclerosis, 121,122 schizophrenia, 123 Parkinson's disease, 124,125 amyotrophic lateral sclerosis, 126 fetal alcohol spectrum disorders, 127 Tourette syndrome, 128 and autism. 129,130 As discussed earlier, MRS/MRSI acquisitions are necessarily long to attain data with sufficient SNR, rendering these acquisitions susceptible to subject and scanner instabilities.…”
Section: Clinical Investigationsmentioning
confidence: 99%
“…% standard deviations) of the fitted spectra exceeded 20% for any metabolite or 40% for myoinositol. 88 At the London site, the participating patients underwent a standardised MRS sequence on a Philips Achieva 3T MRI scanner (Philips Healthcare, Best, the Netherlands) using a 16-channel neurovascular coil. A 15-mm single-slice-thick volume of interest (VOI) was selected for MRS placed superior to the lateral ventricles.…”
Section: Magnetic Resonance Spectroscopymentioning
confidence: 99%
“…Recently, we and others showed that MS lesion characteristics in autopsy tissue are associated with the clinical disease course of MS, in which the proportion of mixed active/inactive (chronic active) lesions was significantly associated with disease progression . This chronic lesion activity is not identifiable with commonly used MRI techniques, although recent 7T MRI and PET‐MRI studies have shown the prognostic potential of these approaches for detection and quantification of these mixed active/inactive lesions in living MS patients .…”
Section: Introductionmentioning
confidence: 98%